2013
DOI: 10.1161/circheartfailure.112.000206
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatility and the Risk of Nonsurgical Bleeding in Patients Supported With the Continuous-Flow Left Ventricular Assist Device HeartMate II

Abstract: Background— Bleeding is an important cause of morbidity and mortality in patients with continuous-flow left ventricular assist devices (LVADs). Reduced pulsatility has been implicated as a contributing cause. The aim of this study was to assess the effects of different degrees of pulsatility on the incidence of nonsurgical bleeding. Methods and Results— The Utah Transplantation Affiliated Hospitals (U.T.A.H.) heart failure and transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
111
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(117 citation statements)
references
References 44 publications
4
111
2
Order By: Relevance
“…There is now strong evidence from multiple centers documenting the relationship between non-invasive measures of pulsatility and AVM GIB. This was first described by Wever-Pinzon et al who reviewed a single center experience of 134 patients and found that the HeartMate II Pulse Index (maximum flow-minimum flow/average flow over 15 seconds) was associated with the risk of non-surgical bleeding in the first 90 days after implantation (19). In a specific analysis of AVM-related GIB the investigators also found a significant association when the Pulse Index was examined as a continuous variable.…”
Section: Role Of Pulsatilitymentioning
confidence: 85%
“…There is now strong evidence from multiple centers documenting the relationship between non-invasive measures of pulsatility and AVM GIB. This was first described by Wever-Pinzon et al who reviewed a single center experience of 134 patients and found that the HeartMate II Pulse Index (maximum flow-minimum flow/average flow over 15 seconds) was associated with the risk of non-surgical bleeding in the first 90 days after implantation (19). In a specific analysis of AVM-related GIB the investigators also found a significant association when the Pulse Index was examined as a continuous variable.…”
Section: Role Of Pulsatilitymentioning
confidence: 85%
“…This index reflects ventricular contractility and correlates with the pulse pressure on arterial pressure tracings. Newer reports indicate this measure of pulsatility is inversely related to GI bleeding, i.e., patients with a higher pulsatility demonstrate lower incidences of GI bleeding (16)(17)(18). Since the artificial pulse in the HM3 is not synchronized with patient heart rate, it may augment or diminish the native pulse.…”
mentioning
confidence: 99%
“…One further non-mechanical issue that has undergone some philosophical changes is the status of the aortic valve opening following LVAD implantation. After concerns arose surrounding progression of aortic regurgitation following LVAD implant, alterations in pump management toward lower speeds in an attempt to foster aortic valve opening were suggested [15]. The benefit of this strategy was felt not only to reduce progression of aortic regurgitation but also to reduce development of gastrointestinal arteriovenous malformations and gastrointestinal bleeding.…”
Section: Potential Causes Of the Problemmentioning
confidence: 99%